2018
DOI: 10.5603/kp.a2018.0146
|View full text |Cite
|
Sign up to set email alerts
|

Heartfelt sepsis: microvascular injury due to genomic storm

Abstract: Sepsis is one of the ten leading causes of death in developed and developing countries. In the United States, sepsis mortality approaches that of acute myocardial infarction and exceeds deaths from stroke. Neonates and the elderly are the most vulner-able patients, with these groups suffering from the highest sepsis mortality. In both groups, many survivors respectively display serious developmental disabilities and cognitive decline. The National Institute of Health/National Heart, Lung, and Blood Institute P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 91 publications
(137 reference statements)
0
19
0
Order By: Relevance
“…Few studies have reviewed the clinical data of SICM after general thoracic surgery. Therefore, our study set out to determine the incidence of SICM among Sepsis is a hyperdynamic process characterized by an increase in cardiac output and low systemic vascular resistance (7)(8)(9). Septic shock is a type of sepsis that manifests with unstable hemodynamics and abnormal metabolism (10,11), for which the mortality rate exceeds 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reviewed the clinical data of SICM after general thoracic surgery. Therefore, our study set out to determine the incidence of SICM among Sepsis is a hyperdynamic process characterized by an increase in cardiac output and low systemic vascular resistance (7)(8)(9). Septic shock is a type of sepsis that manifests with unstable hemodynamics and abnormal metabolism (10,11), for which the mortality rate exceeds 40%.…”
Section: Discussionmentioning
confidence: 99%
“…In MyD88-dependent pathway, MyD88 binds IRAK4, IRAK1, and/or IRAK2, and promotes their binding to TRAF6, then leads to the activation of TAK1 by TRAF6. After a series of activations/reactions, this eventually leads to nuclear translocation of NF-κB, which activates the expression of various inflammatory genes (called gene storms), causing host dysfunction and multiple organ dysfunction (Hawiger, 2018). In MyD88 independent pathways, such as Trif-dependent pathways, Trif interacts with TRAF3 to activate TBK1 and IKKi, and then cause the phosphorylation of IRF3.…”
Section: Toll-like Receptors In Cardiomyocytesmentioning
confidence: 99%
“…Some studies suggested that the pathogenesis of sepsis is the damage of micro-vessels caused by "Genomic Storm" (Hawiger, 2018). Bacteria, fungi, infectious agents and viral nucleic acids bind to TLRs, causing the activation of stress response transcription factors (SRTFs), such as NF-κB, and activated protein 1 (AP-1), which in turn activate multiple genes encoding pro-inflammatory cytokines and chemokines, leading to septic shock and multiple organ dysfunction (Hawiger, 2018). Based on this observation, gene therapy for sepsis and SCM has been proposed.…”
Section: Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The leakage of in ammatory cells into the alveolar cavity is mainly associated by the destruction of the pulmonary microvascular endothelial barrier function, which plays an important role in ALI caused by sepsis [35]. The degree of lung vascular permeability was examined by EB dye.…”
Section: Yqfm Ameliorated Clp-induced Lung Vascular Hyperpermeabilitymentioning
confidence: 99%